Taking the Big Leap | understanding, accessing and improving behavioural science interventions - Gantayat, Nishan; Ashok, Anushka; Manchi, Pallavi; Pierce-Messick, Rosemary; Porwal, Rahul; Gangaramany, Alok (Frontiers in Public Health, 2024)
Applied behaviour science’s focus on individual-level behaviours has led to overestimation of and reliance on biases and heuristics in understanding behaviour and behaviour change. Behaviour-change interventions experience difficulties such as effect sizes, validity, scale-up, and long-term sustainability. One such area where we need to re-examine underlying assumptions for behavioural interventions in Human Immunodeficiency Virus (HIV) and Tuberculosis (TB) prevention, which seek population-level benefits and sustained, measurable impact. This requires taking a “Big Leap.” In our view, taking the big leap refers to using a behavioural science-informed approach to overcome the chasms due to misaligned assumptions, tunnel focus, and overweighting immediate benefits, which can limit the effectiveness and efficiency of public health programmes and interventions. Crossing these chasms means that decision-makers should develop a system of interventions, promote end-user agency, build choice infrastructure, embrace heterogeneity, recognise social and temporal dynamics, and champion sustainability. Taking the big leap toward a more holistic approach means that policymakers, programme planners, and funding bodies should “Ask” pertinent questions to evaluate interventions to ensure they are well informed and designed.